Penggunaan Aplikasi Bealanja Online Perilaku Impulse Buying Mahasiswa FEBI UINSU - Syahfrilla Al Risa Nurul Azmi; Yunda Herliana; Dini Lestari (Universitas Muhammadiyah Enrekang, 2023)
This study aims to analyze and learn more about the impact of online shopping applications on the impulse buying behavior of FEBI UINSU students. The research method used is a qualitative approach using snowball sampling techniques and purposive sampling. This data was collected through interviews and online surveys using the Google Form. The results of this study show that online shopping applications have a significant influence on the impulse buying behavior of FEBI UINSU students. The majority of respondents had experience using online shopping applications, and most of them admitted that they had made impulse purchases after using these applications. Factors such as promotional offers, ease of access, attractive product displays, and social interaction in online shopping applications influence the decision to make impulse purchases. The impact of this impulse buying behavior includes financial problems, anxiety, and post-purchase regret.